Greening and producing: An economic assessment framework for integrating trees in cropping systems. (October 2016) - Van Vooren, Laura; Reubens, Bert; Broekx, Steven; Pardon, Paul; Reheul, Dirk; van Winsen, Frankwin; Verheyen, Kris; Wauters, Erwin; Lauwers, Ludwig
Abstract: Environmental measures in an agricultural context often lead to extra constraints in current farming. This suggests trade-offs between the environmental objectives and profitability. Whether trade-offs exist, or may be turned into win-win, depends on creative farm options to comply new constraints. This paper concentrates on Ecological Focus Areas as a new EU Common Agricultural Policy greening requirement, and investigates profitability changes of two greening options with permanent woody elements, hedgerows and alley cropping. We predicted discounted gross margins for a hedgerow and alley cropping greening option and four market scenarios on a representative arable farm in Flanders (Belgium). Starting from the tree row, over a distance of 1.64 times the tree height, relative crop yield is 70% as compared to a treeless situation. Between 1.64 and 9.52 times the tree height, relative yield is 107%. Beyond that point, the effect is considered negligible. Discounted gross margins are calculated to account for the time horizon. Relative discounted gross margins at farm level, compared to the business as usual option, vary between 91% and 108%, depending on market conditions and policy support. The calculations show that fulfilment of the 5% ecological focus area greening requirement on arable farms with hedgerows and alley cropping only becomes economically competitive to the traditional cropping systems with extra financial stimuli (e.g. greening payments). We also show and discuss how the calculations can be fine-tuned and used in policy making, e.g. by i) getting better insights in the tree-crop interactions, ii) including the effect of e.g. crop type, tree species, tree line space and tree line orientation in the meta-information, iii) evaluating this conditional competitiveness and suggesting a better linking between subsidy level and ecological value and ecosystem services and iv) exploring novel valorization channels for wood products. Highlights: In the new European agricultural policy, greening measures are required. We investigate profitability of alley cropping and hedgerows as greening measures. We develop a tree-crop interaction function. On plot level, hedgerows have less impact than alley cropping on profitability. On farm level, alley cropping has less economic impact, due to hedgerow layout requirements.